Effect of density on the growth of Mesoheros festae fry, with replacement technology (International Seven Journal of Multidisciplinary, 2023)
In Ecuador, inland water fish farming is an activity of growing importance with great economic, social and environmental interest. It involves different productive sectors and native species. (Mesoheros festae), a cichlid, is found along the Pacific drainages, specifically from the Esmeraldas River in Ecuador, through the Guayas River, to the Tumbes River in Peru. The objective of the research was to determine the effect of density on the growth of Mesoheros festae fry in replacement technology. The origin of the specimens belonged to the fish farm of the Faculty of Livestock and Biological Sciences of the State Technical University of Quevedo; the average initial weight of the animals was 1.5 g. Sixteen circular cages made of plastic mesh were used, with the following dimensions: 0.50 m in diameter and 0.90 m in height and 0.5 inch mesh eye, the pond measures 7 m by 4 m, x 0.80 m, provided with water inlet and outlet, the water replacement was 30% daily. The fry of M. festae used in the present work had an average initial weight of 1.5 grams, which were fed with a balanced extruded feed for tilapia containing 38% protein. The final weight 56 days after the experiment the fry of the three treatments presented the following reports: Treatment 1: 4.7 ±0.87 a; Treatment 2: 5.3 ±0.16 treatment T3 6. 2 ±0.64, the results presented statistical differences between treatments.